2018
DOI: 10.1213/xaa.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag to Treat Thrombocytopenia During Last Month of Pregnancy in a Woman With MYH9-Related Disease

Abstract: MYH9-related disease (MYH9-RD) is an inherited rare autosomal dominant macrothrombocytopenia. Patients with MYH9-RD have giant platelets and leukocyte inclusion bodies caused by mutations in the MYH9 gene encoding the non-muscle myosin heavy chain II-A. Before identification of the causative gene, patients were diagnosed as Epstein or Fechtner or Sebastian syndromes or May-Hegglin anomaly. As with other inherited thrombocytopenias, the risk of increased bleeding during perioperative period or delivery is a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…After 3–6 weeks of treatment, platelet response was observed in nearly all patients (11 of 12), and remission of spontaneous bleeding was achieved in eight of 10 patients who had this feature at baseline . On the basis of these results, three patients with MYH9 ‐RD and severe thrombocytopenia received eltrombopag as the only treatment in preparation for planned hemostatic challenges: an adult female patient who needed to undergo major orthopedic surgery , a child requiring tympanoplasty , and another adult female patient in the last month of pregnancy for whom a cesarean delivery had been planned . In all of these patients, platelet counts greatly increased.…”
Section: Tpo‐rasmentioning
confidence: 99%
See 2 more Smart Citations
“…After 3–6 weeks of treatment, platelet response was observed in nearly all patients (11 of 12), and remission of spontaneous bleeding was achieved in eight of 10 patients who had this feature at baseline . On the basis of these results, three patients with MYH9 ‐RD and severe thrombocytopenia received eltrombopag as the only treatment in preparation for planned hemostatic challenges: an adult female patient who needed to undergo major orthopedic surgery , a child requiring tympanoplasty , and another adult female patient in the last month of pregnancy for whom a cesarean delivery had been planned . In all of these patients, platelet counts greatly increased.…”
Section: Tpo‐rasmentioning
confidence: 99%
“…Earlier findings with romiplostim in patients with MDS showed increased bone marrow blast counts, and suggested a potential risk of AML progression [52][53][54]. More recently, it was reported that patients with low-risk MDS who received romiplostim for 58 weeks did not have significantly higher AML progression rates 5 years after discontinuation, indicating that the effects of romiplostim on blast counts and, potentially, AML progression are • Clinical trial with eltrombopag (n = 12): after 3-6 weeks of treatment, a platelet response was observed in 92% of patients, and bleeding symptoms were normalized in 80% of patients [26] • Case studies with eltrombopag: platelet counts increased to allow surgery in two adult females and a child [27][28][29]. In all patients, the surgical procedures were performed without complications and with no use of platelet transfusions…”
Section: Risk Of Hematological Malignancymentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports have demonstrated successful avoidance of platelet transfusions and bleeding when eltrombopag was given prophylactically to patients with MYH9-related disease who were undergoing surgery or cesarean delivery. 43,44 One study of eltrombopag in WiskottAldrich syndrome or X-linked thrombocytopenia showed improved platelet counts but persistent defects in platelet activation. 45 Although eltrombopag has been approved for use as a therapy for refractory chronic ITP in children, the authors of this study have used eltrombopag to treat severe, refractory bleeding in patients with acute ITP at the time of presentation.…”
Section: Other Indications and Future Directionsmentioning
confidence: 99%
“…However, clinical evidence on this matter is still scarce: only three single case reports have described successful surgery after eltrombopag administration. 4 Since 2010, we proposed short-term eltrombopag to all patients with MYH9-RD who needed elective surgery and had a platelet count too low for a safe procedure according to the current guidelines. 5 All patients accepted this treatment.…”
Section: O R R E S P O N D E N C Ementioning
confidence: 99%